Social boundaries and social-political categories in Early Imperial Roman History - Faversani, Fabio (Romanitas - Revista de Estudos Grecolatinos, 2018)
This article discusses different historiographical approaches that dominated the studies on early imperial Roman history during the 20th and the beginning of the 21st century. In order to do this, it focuses on two historiographic controversies: in the first place, the modernist-primitivist debate concerning economic history; in the second place, the debate about the constitutionalist approach to Roman politics, and the criticism it attracted. We conclude that historians have paid great attention to the elements that characterize the different spheres of social life, and to the reasons why scholars ought to favour one of them - especially whether to consider more structural or more dynamic aspects of social life. Our article considers the challenges in surveying the elements that integrate and separate these different spheres, i.e. the frontiers, suggesting possible approaches to overcome these limits, mainly by paying attention to their boundaries and connections.
Keywords: Império Romano; Historiografia; História Antiga; Sêneca; Tácito